A contribuição da inteligência artificial (IA) na filosofia da mente - Nakabayashi, Luciana Akemi (2009)
The current research has as central theme investigate the concept of intelligence, and specifically of Artificial Intelligence (AI), derived from the Computer Science and its effect on research of Philosophy of Mind. It tries to consider and to understand such perspective to the light of Technoscience and Cybernetics, in view of the concepts that look for to understanding the human mind by the imitation of its behavior, applying the concepts to the investigation and simulation of dialogues: called Chatterbots. The research stars from a methodological and bibliographic study diverse from the concepts of Artificial Intelligence (AI) and the concepts of Philosophy of Mind, focusing on the prominence of the issue in its interdisciplinary aspects. Discusses the prospects consolidated in the community about the issue, especially the approaches of Searle (1984, 1992, 1997), Gardner (1994, 1995) and, in the Brazilian landscape, from Teixeira (1990, 1994, 1995, 1998, 2000, 2004, 2008), focusing on relations between the concepts of intent, brain, mental and cognitive experiment, as well as some trends of criticism and defense of its formal limits. Drawing up of previous searches on the subject and methodology that merges computing elements and philosophy of mind, analyzes the conceptual experiment of the Chinese Room of Searle (in aspects of syntax and semantics). From this experiment and its results, it presents the prospect of Artificial Intelligence (AI) investigation as belonging to the nature of cognition, supported by the theory of cognition, particularly for phenomena such as categorization and identification of objects, problem solving, decision and conscience. The search culminates in the analysis of the concept of Artificial Intelligence (AI) in Philosophy of Mind, proposed as a noematic element, being constituted as prerequisite for the production of scientific knowledge, implemented in the areas of Intelligence Technology and Digital Design. Applies the concepts and achievements to the definition and extension of the concept of hypertext, taking it as a computational mechanism capable of structuring hierarchical dialogues, indexed, so as to the formulation of Robot Primo (2001) and Roth Coelho (2001). Finally, the assumptions investigated are shown in results observed in the so-called Chatterbots in the area of Artificial Intelligence (AI), highlighting its characteristics and its importance in the current context of its computer utilization in cyberspace